A Cross-Sectional Survey on COVID-19 Vaccine Hesitancy Among Parents From Shandong vs. Zhejiang - Xu, Yunyun; Xu, Dongjuan; Luo, Liyan; Ma, Fengqiao; Wang, Ping; Li, Hongfei; Li, Qing; Wei, Lianyan; Diao, Jiuzhou; Liu, Yuanyuan; Zhang, Weiqiang; Zheng, Xiaolei (Frontiers in Public Health, 2021)
Introduction: With the approval of COVID-19 vaccinations for children and adolescents in China, parental vaccine hesitancy will emerge as a new challenge with regard to the administration of these vaccines. However, little is known regarding this hesitancy as well as regional differences that may exist between parents from Shandong versus Zhejiang. Methods: To assess these issues, an online survey was conducted via a Wenjuanxing platform over the period from July 22 to August 14, 2021. Parents from Shandong and Zhejiang were recruited from Wechat groups and results from a total of 917 subjects were analyzed. Factors evaluated in this survey included socio-demographic variables, parental vaccine hesitancy, Parental Attitudes towards Childhood Vaccines (PACV) domains (behavior, safety and efficacy, general attitudes) and social support. Results: Compared with those from Shandong (N = 443), parents from Zhejiang (N = 474) showed significantly higher prevalence rates of COVID-19 vaccine hesitancy (19.4 vs. 11.7%, p = 0.001). Multivariate logistic regression showed that yearly household incomes of ≥120,000 RMB (p = 0.041), medical workers (p = 0.022) and general attitudes of PACV (p = 0.004) were risk factors for vaccine hesitancy among parents from Shandong, while behavior (p = 0.004), safety and efficacy (p < 0.001) and general attitudes of PACV (p = 0.002) were risk factors for parents from Zhejiang. Among parents with vaccine hesitancy (N = 144), concerns over side effects (91.0%) and unknown effects (84.0%) of the COVID-19 vaccine were the most prevalent reasons for hesitancy. Evidence providing proof of vaccine safety (67.4%) and assurance of a low risk for side effects from the vaccine (54.2%) were the two most effective persuasive factors. Conclusion: Parents from Zhejiang showed a higher prevalence of COVID-19 vaccine hesitancy as compared with those from Shandong. Behavior, safety and efficacy, and general attitudes of PACV were the risk factors associated with this hesitancy in these parents from Zhejiang. Given the identification of the various reasons for parental vaccine hesitancy, different strategies as well as regional adjustments in these strategies will be required for an effective and convincing protocol for childhood vaccinations.